Sistem Informasi Pelayanan Imunisasi Dan Tumbuh Kembang Balita Berbasis Web Pada Posyandu Sartika Melati I - Hasibuan, Laila Fitriani (Universitas Multi Data Palembang, 2024)
The process of storing immunization and weighing data that is currently running at Posyandu Sartika Melati I is still conventional. Starting from the registration stage, weighing records, immunization records, and recording the results of posyandu activities are still handwritten. To speed up data management, it is necessary to create a web-based immunization and weighing service information system. The system development method used in this design is the waterfall method, with the design of the Usecase diagram, Activity diagram, and Entity Relationship Diagram then implemented into the PHP programming language and MySQL database. The result of the design is a system that can manage child registration data, weighing data, immunization data, schedule information, and posyandu reports that are more quickly accessible and accurate.